Odpowiedź :
a) y= 3/2x
x = 2 ; y = 3/2 *2 = 3
x = 4 ; y = 3/2*4 = 6
x=(-2) ; y = 3/2 *(-2) = -3
x =0 ; y =0
b) y= -0,2x - 3
x = 10 ; y = -2-3 = -5
x=0 ; y= (-3)
x = 5 ; y = -1/5 *5 - 3 = -4
x = -10 ; y = -1
c) y= - 3/2 ( - 3/2 to ułamek )
x = 2 ; y = -3/2 *2 = -3
x = 4 ; y = -3/2*4 = -6
x=(-2) ; y = -3/2 *(-2) = 3
x =0 ; y =0
x = 2 ; y = 3/2 *2 = 3
x = 4 ; y = 3/2*4 = 6
x=(-2) ; y = 3/2 *(-2) = -3
x =0 ; y =0
b) y= -0,2x - 3
x = 10 ; y = -2-3 = -5
x=0 ; y= (-3)
x = 5 ; y = -1/5 *5 - 3 = -4
x = -10 ; y = -1
c) y= - 3/2 ( - 3/2 to ułamek )
x = 2 ; y = -3/2 *2 = -3
x = 4 ; y = -3/2*4 = -6
x=(-2) ; y = -3/2 *(-2) = 3
x =0 ; y =0
a) y=3/2x
x=-3, 3
y=-1/2,1/2
b) y=-0,2x-3
x=-5,5
y=-4,-2
-0,2=1/5
c)y=-3/2
x=2,3,4,5 (to dowolne liczby bo to jest funkcja stała)
x=-3, 3
y=-1/2,1/2
b) y=-0,2x-3
x=-5,5
y=-4,-2
-0,2=1/5
c)y=-3/2
x=2,3,4,5 (to dowolne liczby bo to jest funkcja stała)